THE MITE Steneotarsonemus pallidus NEW STRAWBERRY PLAGUE IN COLOMBIA AND A STUDY ON ITS CHEMICAL CONTROL AND DISSEMINATION TO OTHER CROPS - URUETA-SANDINO, EDUARDO J.; NAVARRO-ALZATE, RAFAEL (Revista Colombiana de Entomología, 1978)
The cyclamen mite, Steneotarsonemus pallidus (Banks) was found for the first time, affecting several strawberry plantations located in Departamento de Antioquia, Colombia, during 1977. A trial to control the mite was carried out using the following pesticides: Calcium polisulfide 5%; diazinon 0,06%; dicofol 0,04%; endosulfan 0,11 %; fenitrothion 0,1 % and tetradifon 0,06%. The best treatment was endosulfan 0,11 %. Dicofol 0,04% also affected good control. All other treatments were not very effective in controlling this pest. Steneotarsonemus pallidus (Banks) failed to be established on two varieties of chrysanthemum, under greenhouse conditions.